Analysis On Effect Of Ball Bladder Size During Water Hammer In Domestic Water System - Mohd Nasir, Faarih Farhan (2017)
This project is studying the effect of ball bladder size on hydraulic shock during water hammer for a domestic water system. Water hammer is a common phenomenon when pipe in our home is shut down suddenly and can cause pump failures, water system fatigue, pipe rupture and contaminated water backflow. Thus, produce loud banging or hammering noise. To prevent this phenomenon, a suitable accumulator is a must. A ball bladder type of accumulator has been chosen due to its flexibility, light in weight and capability to absorb the hydraulic shock during water hammer. There will be two parameters for the experiment, which are; pressure of water during water hammer and effect of ball bladder size on hydraulic shock. Then, these parameters will be the analysis for reducing the effect of water hammer for the future. The experiments were conducted by using DAQami software in order to understand the behaviour of the shock wave due to water hammer with the present of ball bladder. Therefore, from the analysis result, the accumulator with four ball bladders with the size of 862.52 cm3 has the slowest time of water pressure increase when the test valve is shut down suddenly, no leaking at pipeline, no water droplets came out of the leaking and the sound of the pump is not noisy when the test valve is shut down immediately or suddenly. Besides that, the pressure of the shock wave is being reduced from 4.00 bar to 2.79 bar which was reduced to 1.21 bar (30%). Thus, an appropriate size of ball bladder will be determined for the domestic water system to prevent the water hammer with the size of 1523 cm3 approximately to seven ball bladders.